2015
DOI: 10.1038/srep08846
|View full text |Cite
|
Sign up to set email alerts
|

CD47 Deficiency Protects Mice From Diet-induced Obesity and Improves Whole Body Glucose Tolerance and Insulin Sensitivity

Abstract: CD47 is a transmembrane protein with several functions including self-recognition, immune cell communication, and cell signaling. Although it has been extensively studied in cancer and ischemia, CD47 function in obesity has never been explored. In this study, we utilized CD47 deficient mice in a high-fat diet induced obesity model to study for the first time whether CD47 plays a role in the development of obesity and metabolic complications. Male CD47 deficient and wild type (WT) control mice were fed with eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 55 publications
3
47
1
Order By: Relevance
“…Conversely, in mouse models, CD47-deficient mice show decreased weight gain on high-fat diets, increased energy expenditure, improved glucose profile and decreased inflammation26.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, in mouse models, CD47-deficient mice show decreased weight gain on high-fat diets, increased energy expenditure, improved glucose profile and decreased inflammation26.…”
Section: Resultsmentioning
confidence: 99%
“…No genome-wide significant associations have been reported for the lead SNP or other SNPs in the CD47 gene before232425. However, a recent study revealed a link to diet-induced obesity in mice and suggests CD47 as a potential drug-target to combat obesity and metabolic complications2627.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was extracted from subcutaneous white adipose tissue (WAT) by the DNAeasy Blood and Tissue kit (Qiagen, Germantown, MD, http://www.qiagen.com). QPCR was performed on COX1 mitochondrial DNA and normalized to a nuclear 28S sequence . The sequences of primer sets used in this study are listed in Supporting Information Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Germantown, MD, http://www.qiagen.com). QPCR was performed on COX1 mitochondrial DNA and normalized to a nuclear 28S sequence [28,29]. The sequences of primer sets used in this study are listed in Supporting Information Table 1.…”
Section: Stem Cellsmentioning
confidence: 99%